Journey to the center of the earth (2008) [videorecording (DVD)] - Fraser, Brendan, 1968-; Hutcherson, Josh; Briem, Anita; Meyers, Seth, 1973-; Verne, Jules, 1828-1905 (New Line Home Entertainment : Warner Home Video, 2008)
Science professor Trevor Anderson's radical theories have tarnished his reputation. While backpacking across Iceland with his nephew Sean, the two find a cave that leads them deep down into the bowels of the planet. They go on a quest to find out what has happened to Trevor's missing brother, also a scientist. Trevor, Sean and their mountain guide discover a fantastic and dangerous lost world in the center of the earth. There, they discover a bizarre landscape filled with terrifying creatures.